AZO transparent electrodes grown in situ during the deposition of zinc acetate dihydrate onto aluminum thin film by spray pyrolysis - Ozório, Maíza S. [UNESP]; Nascimento, Mayk R. [UNESP]; Vieira, Douglas H. [UNESP]; Nogueira, Gabriel L. [UNESP]; Martin, Cibely S. [UNESP]; Lima, Sergio A. M. [UNESP]; Alves, Neri [UNESP] (Springer Nature, 2019)
Zinc acetate dihydrate solution was deposited onto glass and a thin layer of aluminum (10 nm), by spray pyrolysis at 450 °C, growing zinc oxide (ZnO) thin films. The ZnO formation occurs differently on aluminum due to the diffusion process forming AZO at the Al/ZnO interface. The films deposited onto the aluminum showed transmittance above 95%, associated with sheet resistance less than 40 Ω/sq. The high transmittance value with low sheet resistance is crucial for a good transparent electrode. Raman spectroscopy showed a higher degree of doping for films with thin layers of ZnO, and that the diffusion process is high at the Al/ZnO interface. The performance of the transparent electrode was evaluated through the characterization of the Schottky diode (Al:ZnO/ZnO/Au). The factor of ideality (n), resistance in series (Rs), and height of the barrier (ϕB) presented values of 3.79, 1022.6 Ω, and 0.97 eV, respectively. These results demonstrate the simple production of a transparent electrode by the in situ diffusion process using the spray pyrolysis technique.